The Application of Pulmonary Ultrasound in Neonatal Ventilator-Associated Pneumonia - Jiang, Peng; Wei, Jing (Frontiers in Pediatrics, 2022)
This study explored the application value of lung ultrasound (LUS) in neonatal ventilator-associated pneumonia (NVAP). In this study, 122 newborns suspected of NVAP were treated in the NICU of Liaocheng People's Hospital between July 1, 2020, and July 1, 2021. Of these, 115 were clinically diagnosed with NVAP. The diagnostic value of LUS for NVAP was determined by comparing the different signs of LUS and chest X-ray (CXR). The confirmed cases were divided into the failure and success groups according to the first ventilator weaning test results. The consistency between the results of LUS and CXR and the actual test results was compared between the two groups. Before treatment, the LUS findings of the confirmed cases showed a lung consolidation with air bronchogram sign (111/115), alveolar-interstitial syndrome (113/115), pleural effusion (12/115), pleural line abnormalities (114/115), and lung pulse (15/115). CXR showed 109 cases of pneumonia. Taking the clinical diagnosis of VAP as the gold standard, the lung consolidation with air bronchogram sign on LUS had a higher sensitivity, specificity, and accuracy for the diagnosis of NVAP than those of other LUS and CXR findings and showed better consistency with the clinical diagnosis (AUC=0.983, kappa value = 0.761, P < 0.05). After treatment, the 115 cases were divided into two groups according to the results of the first weaning from ventilation: the failed group (19 cases) and the successful group (96 cases). The lung consolidation with air bronchogram sign was used as the positive diagnostic standard of ultrasound. The sensitivity and specificity of LUS (94.7%, 89.6%) in evaluating the outcome of weaning from the ventilator of pneumonia were higher than those of CXR (73.7%, 84.4%). Additionally, the consistency of the LUS findings with the weaning results was higher than that of CXR (AUC=0.922, kappa value = 0.709, P <0.05). Therefore, compared with CXR, LUS has a higher value in diagnosing NVAP and can better predict the results of the ventilator off-line test. LUS can replace CXR as the first imaging examination for NVAP.